2016
DOI: 10.1016/j.phrs.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A PRISMA-compliant systematic review and meta-analysis of randomized controlled trials investigating the effects of statin therapy on plasma lipid concentrations in HIV-infected patients

Abstract: Statin therapy may lower plasma lipid concentrations, but the evidence in HIV-infected patients is still unclear. Therefore, we aimed to investigate the impact of statin therapy on plasma lipid concentrations through a systematic review of the literature and meta-analysis of available randomized controlled trials (RCTs). The literature search included PUBMED, SCOPUS, Web of Science and Google Scholar up to October 30, 2015. The meta-analysis was performed using either a fixed-effects or random-effect model acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
23
1
Order By: Relevance
“…More recent studies have focused on therapies that reduce immune activation, as well as cholesterol, which may be of benefit, particularly for HIV + individuals because the CVD is driven by traditional and inflammatory factors (3,123). Statins, which are both lipid-lowering and anti-inflammatory, were used in the INTREPID (HIV+ Patients and Treatment with Pitavastatin vs Pravastatin for Dyslipidemia) and the current REPRIEVE (Randomized Trial to Prevent Vascular Events in HIV) trial.…”
Section: Clinical Trials Of Hiv-associated Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have focused on therapies that reduce immune activation, as well as cholesterol, which may be of benefit, particularly for HIV + individuals because the CVD is driven by traditional and inflammatory factors (3,123). Statins, which are both lipid-lowering and anti-inflammatory, were used in the INTREPID (HIV+ Patients and Treatment with Pitavastatin vs Pravastatin for Dyslipidemia) and the current REPRIEVE (Randomized Trial to Prevent Vascular Events in HIV) trial.…”
Section: Clinical Trials Of Hiv-associated Atherosclerosismentioning
confidence: 99%
“…Recent trials (127) indicate that rosuvastatin decreases oxLDL levels early after initiation and is associated with decreased monocyte activation (3,123). This early improvement in oxLDL is linked with improved CIMT, a measurement for atherosclerotic plaque in treated HIV infection (3,123).…”
Section: Clinical Trials Of Hiv-associated Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia is a leading risk factor for cardiovascular morbidities and mortalities. In spite of the established role of statins as the mainstay of lipid management (Banach & Serban, et al, ; Banach et al, , ) and numerous pleiotropic actions of these drugs (Chrusciel et al, ; Ferretti, Bacchetti, & Sahebkar, ; Parizadeh et al, ; Sahebkar & Kotani, et al, ; Sahebkar & Serban, et al, ; Serban et al, ), statin‐treated patients have a considerable residual cardiovascular risk that calls for additional LDL lowering (Banach & Aronow, et al, ; Sahebkar & Watts, , ). PCSK9 inhibitors such as evolocumab (formerly AMG 145) and alirocumab (formerly REGN727/SAR236553), are human monoclonal antibodies (mABs) that bind with a high affinity to PCSK9 and suppress its function resulting in a reduction of LDL‐cholesterol levels (Blom et al, ; Giugliano et al, ) and cardiovascular events (Sabatine et al, ).…”
Section: Pcsk9 Inhibitors and Risk Of Infection In Clinical Trialsmentioning
confidence: 99%
“…Specifically, concern on the use of PCSK9 inhibitors in HCV-infected patients cannot be easily translated to HIV patients, where cholesterol-lowering treatment is often indicated (e.g. statins) and in some cases hampered by drug-to-drug interactions [90]. Conversely, preclinical and clinical studies showed that PCSK9 inhibition promotes pathogen lipid clearance by LDLR, reduces inflammatory signals and improves prognosis among patients with sepsis [15,91].…”
Section: The Interaction Between Hcv and Pcsk9mentioning
confidence: 99%